Analysis of reproductive outcomes after cesarean scar pregnancy surgery: a multicenter retrospective study - Yin, Yin; Huang, Limei; Xu, Nuo; Ma, Huagang; Yuan, Chaoyan (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to analyze the outcome of postoperative re-pregnancies in patients with a cesarean scar pregnancy (CSP) and investigate the factors influencing the occurrence of recurrent cesarean section scar pregnancy (RCSP).MethodsA retrospective analysis was performed on the clinical data of 105 patients with CSP who had undergone surgical treatment and were admitted to the Minda Hospital affiliated with Hubei University for Nationalities, Henan Provincial People’s Hospital, Linyi People’s Hospital, and Weifang People’s Hospital from January 2015 to May 2021. The reproductive outcomes of these patients were monitored, and the factors influencing the occurrence of RCSP were analyzed.ResultsIn this study, it was found that the reproductive outcomes of patients with CSP after surgery included ectopic pregnancy, normal intrauterine pregnancy, RCSP, and abortion. The postoperative re-pregnancy rate was 51.72% (105/203), and the postoperative RCSP rate was 13.33% (14/105). The number of cesarean sections (OR = 2.004, 95% CI: 1.412–22.579, p < 0.001) was identified as an independent risk factor for the occurrence of RCSP, and the intraoperative removal of the uterine scar (OR = 0.045, 95% CI: 0.005–190.400, p = 0.002) was determined as an independent protective factor for the occurrence of RCSP.ConclusionFor patients with residual reproductive requirements after CSP surgery, the removal of uterine scar tissue during the operation can be contemplated. Subsequent postoperative re-pregnancy demands close surveillance and follow-up during gestation, with appropriate termination of pregnancy when warranted. For patients without reproductive needs after surgery, contraception is recommended to prevent the occurrence of RCSP.